Determining the Effect of Science Teaching Using Mobile Augmented Reality Application on the Secondary School Students’ Attitudes of toward Science and Technology and Academic Achievement - Kececi, Gonca; Yildirim, Pelin; Zengin, Fikriye Kirbag (International Council of Associations for Science Education (ICASE), 2021)
In this research, the effects of science education using mobile augmented reality (MAR) application on students’ attitudes toward science, technology, and their academic achievement were determined against two socioeconomic levels. The parallel pattern mixed method was used in the study. The research was carried out with 143 sixth-grade students from two schools with different socioeconomic levels in Turkey. The MAR application was used with the experimental groups. Quantitative data were collected through the “Science and Technology Attitude Scale” and “Systems Achievement Test.” According to the ANCOVA results, it was observed that the MAR application used in the processing of the lessons was effective in improving the academic achievement levels of the students but not in attitudes toward science and technology. Results showed that the socioeconomic situation played an active role on the academic achievement of students but did not play an effective role on science and technology attitudes. The results of this research are important in determining the differences between students at different socioeconomic levels experiencing technology-supported systems. © 2021 Science Education International. All rights reserved.
Keywords: academic achievement; attitude; mobile augmented reality; science teaching